Parametric study on catalytic cracking of LDPE to liquid fuel over ZSM-5 zeolite - Wong, S. L. (Elsevier Ltd, 2016)
Pyrolysis or cracking of plastic waste is considered as a potential solution to the environmental problems brought about by plastic waste, with the production of hydrocarbon fuel as a value added benefit. In order to explore the potentials of such process, parametric study have been conducted on the catalytic cracking of LDPE dissolved in benzene in a fixed bed reactor. The five factors studied were temperature (A), catalyst mass (B), feed flow rate (C), carrier gas flow rate (D), as well as concentration of LDPE solution (E), while the responses were LDPE conversion (Y1) and liquid yield (Y2). The parametric study showed that four out of five factors (A, B, C and D) have significant effects on Y1 and Y2. The optimum conditions that produced maximum responses for Y1 and Y2 simultaneously are 600 °C (A), 0.10 g catalyst (B), 1 ml/s LDPE solution (C), 80 ml/min N2 flow (D). The numerical values for Y1 and Y2 were 98.6% and 99.5%, respectively. Analysis on products composition indicated that catalytic cracking of LDPE in fixed bed reaction generally produced high amount of aliphatic branched-chain compounds, together with moderate amount of cyclic compounds. Aromatization of LDPE cracking products is less due to the short retention time of the compounds on the catalysts bed.